2018
DOI: 10.1177/0022243718820548
|View full text |Cite
|
Sign up to set email alerts
|

The Visual Asymmetry Effect: An Interplay of Logo Design and Brand Personality on Brand Equity

Abstract: Five studies using a variety of experimental approaches and secondary data sets show that a visual property present in all brand logos—the degree of (a)symmetry—can interact with brand personality to affect brand equity. Specifically, compared with symmetrical logos, asymmetrical logos tend to be more arousing, leading to increased perceptions of excitement. As such, consumers tend to perceive asymmetrical logos as more congruent with brands that have an exciting personality. This can boost consumers’ evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 71 publications
4
85
0
1
Order By: Relevance
“…Research into the design of brand logos has found that careful consideration and execution of elements like color (Foroudi et al 2014;Henderson & Cote 1998;Labrecque & Milne 2012;Müller, et al 2013;Klink 2003), complexity (Henderson & Cote 1998;Grinsven & Das 2014;Luffarelli et al 2019. ) and shape (Walsh 2005;Jiang et al 2016;Pittard et al 2007;Luffarelli et al 2019. ) have positive effects on consumer brand recognition, brand liking, and brand personality.…”
Section: Conceptual Background Brand Logos and Brand Personalitymentioning
confidence: 99%
See 4 more Smart Citations
“…Research into the design of brand logos has found that careful consideration and execution of elements like color (Foroudi et al 2014;Henderson & Cote 1998;Labrecque & Milne 2012;Müller, et al 2013;Klink 2003), complexity (Henderson & Cote 1998;Grinsven & Das 2014;Luffarelli et al 2019. ) and shape (Walsh 2005;Jiang et al 2016;Pittard et al 2007;Luffarelli et al 2019. ) have positive effects on consumer brand recognition, brand liking, and brand personality.…”
Section: Conceptual Background Brand Logos and Brand Personalitymentioning
confidence: 99%
“…While studies have looked at elements like complexity (Grinsven & Das 2014;Luffarelli et al 2019. ) and color (Foroudi et al 2014;Henderson & Cote 1998;Labrecque & Milne 2012;Müller et al 2013;Klink 2003) in logo design to create desirable brand image equity, empirical research into the shape of a brand logo in this aspect has been minimal, most likely due to the subjective nature of what makes "good" design.…”
Section: Logo Shapementioning
confidence: 99%
See 3 more Smart Citations